Cyber Security in Smart Cities: Role of 5G Technologies the Indian Perspective - Putarjunam R,; Kala N, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The UN-Habitat World Cities Report 2022 published in June 2022 states that, population in urban areas of India is estimated to reach at 675 million and will be 43.2 percent of its total population by 2035. It will be the second highest figure, behind China’s one billion. In last two decades, India and China experienced rapid urbanization and economic growth. As a result, number of people living in poverty reduced [1]. The Government of India launched “The Smart Cities Mission (SCM)” on 25 June 2015[2]. The aim is to spearhead development and quality of life in urban areas with the help of IT and IT enabled services. The smart cities in India though growing in numbers are more of an up-gradation of the old legacy township where the basic amenities and infrastructure are being given a fresh look with implementation of the modern tools and development techniques. Presently many legacy manual systems for essential services like power, water, communication, transport and many public distribution systems lack the resources and capacity to meet the growing demand and aspirations of people. Most smart cities are seeing uncontrolled and uncoordinated developments with various agencies working in their comfort zones and SILOS have failed to adequately address the role of cyber security that comes as potential risk with such modern IT enabled services. Adherence to standards and protocols for cyber security in the smart city sector are mostly missing or being adopted in an adhocmanner.Since the concept of changing urban life style in the Smart Cities is in a very nascent stage, it throws lot of challenges for the administration to deal with issues of cyber attacks. This research is aimed at identification and analysisof potential cyber security risks and challenges of smart cities. The focus will be to understand the entire ecosystem of smart city challenges and desired security standards, various security regulatory frameworks in world &India and how they can be adopted to the Indian scenario. Further the latent capabilities and advantages of using 5G technology has been touched upon in conjunction with how its adoption id developing the Smart Cities can help. This research finally proposes a way ahead to an integrated approach to smart city development, exploiting the available technologies.
Keywords: Smart City; Ecosystem; Urbanization; Challenges; Information; Communications; Technology; Internet of Things; Cyber Security; Threat; Connectivity; 5G